2010
DOI: 10.1152/ajplung.00421.2009
|View full text |Cite
|
Sign up to set email alerts
|

CFTR and calcium-activated chloride channels in primary cultures of human airway gland cells of serous or mucous phenotype

Abstract: Using cell culture models, we have investigated the relative importance of cystic fibrosis transmembrane conductance regulator (CFTR) and calcium-activated chloride channels (CaCC) in Cl secretion by mucous and serous cells of human airway glands. In transepithelial recordings in Ussing chambers, the CFTR inhibitor CFTR(inh)-172 abolished 60% of baseline Cl secretion in serous cells and 70% in mucous. Flufenamic acid (FFA), an inhibitor of CaCC, reduced baseline Cl secretion by ∼20% in both cell types. Methach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
4
36
0
Order By: Relevance
“…Effectors that are specific for increasing intracellular Ca 2ϩ such as carbachol, histamine, methacholine, and ATP as well as effectors such as forskolin that increase cAMP all increase Cl Ϫ /HCO 3 Ϫ secretion (1,11,21,22,26,36). In this regard, results in the Calu-3 cell line agree with both human and porcine primary cultures (11,40).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Effectors that are specific for increasing intracellular Ca 2ϩ such as carbachol, histamine, methacholine, and ATP as well as effectors such as forskolin that increase cAMP all increase Cl Ϫ /HCO 3 Ϫ secretion (1,11,21,22,26,36). In this regard, results in the Calu-3 cell line agree with both human and porcine primary cultures (11,40).…”
Section: Discussionsupporting
confidence: 55%
“…However, in addition to the importance of Ca 2ϩ -activated K ϩ channels, more recent studies have demonstrated the presence of an apical CaCC. TMEM16A is highly expressed in secretory epithelial tissues, where it has been implicated to play a key role in Ca 2ϩ -dependent Cl Ϫ secretion (6,11,28,29,41). Fischer and colleagues (11) identified TMEM16A mRNA in both human serous cells and in the Calu-3 cell line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence for fluid secretion by mucous cells of native glands (67). Finally, mucous cultures contain both CFTR and calcium-activated chloride channels as revealed by patch clamping and Ussing chamber studies (22). Therefore, it is possible that alterations in secretion of Cl Ϫ (or mucins) by mucous cells may contribute to the abnormally concentrated gland secretions in CF.…”
Section: Discussionmentioning
confidence: 99%